2016
DOI: 10.1016/j.celrep.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Allelic Frequency and CDRH3 Region Limit the Engagement of HIV Env Immunogens by Putative VRC01 Neutralizing Antibody Precursors

Abstract: SUMMARY Elicitation of broadly neutralizing antibodies remains a long-standing goal of HIV vaccine research. Although such antibodies can arise during HIV-1 infection, gaps in our knowledge of their germline, pre-immune precursor forms, as well as on their interaction with viral Env, limit our ability to elicit them through vaccination. Studies of broadly neutralizing antibodies from the VRC01-class provide insight into progenitor B cell receptors (BCRs) that could develop into this class of antibodies. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 48 publications
6
49
0
Order By: Relevance
“…Among this donor’s VRC01-class naive B cells, 89% expressed a kappa variable (Vκ) LC (25 of 28, Figure 1B). κ + VRC01-class bnAbs use a consensus Gln-Gln-Tyr-Glu-Phe (QQYEF) L-CDR3 sequence (20, 21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among this donor’s VRC01-class naive B cells, 89% expressed a kappa variable (Vκ) LC (25 of 28, Figure 1B). κ + VRC01-class bnAbs use a consensus Gln-Gln-Tyr-Glu-Phe (QQYEF) L-CDR3 sequence (20, 21).…”
Section: Resultsmentioning
confidence: 99%
“…Here we found a modest inverse correlation between H-CDR3 length and affinity of naive VRC01-class B cells to eOD-GT8, suggesting slight preferential binding by BCRs with shorter H-CDR3s (p = 0.03, r = 0.28; Figure 2E). A tryptophan (Trp) at the −5 position from the end of the H-CDR3 is present in most VRC01-class bnAbs (also known as Trp100B in VRC01) (20, 28). Although eOD-GT8 was not specifically designed to favor this VRC01-class feature, 31% of VRC01-class naive B cells did contain a Trp at this position (Figure 2F, 21 of 67 with complete HC sequences).…”
Section: Resultsmentioning
confidence: 99%
“…Although putative bNAb precursors have been discovered in HIV-naive repertoires ( Jardine et al., 2016 , Yacoob et al., 2016 ), it is unclear how the antibody repertoires of HIV-infected individuals change from the time before infection through different stages of infection. Furthermore, while ontogeny and structural studies of HIV-reactive antibodies have revealed convergence at the structural level in multiple donors ( Scheid et al., 2011 , Wu et al., 2011 , Zhou et al., 2015 ), the overall differences and similarities in the antibody repertoires of HIV-infected donors have not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, antibodies of this class are particularly restricted for usage of the VH1-2*02 allele and a 5 amino acid CDRL3 [101]. BCR repertoire analyses revealed that potential VRC01-class precursor B cells are exceptionally rare [147][148][149]. In addition, allelic variation can result in the lack of naïve B cells derived from the key VH1-2*02 allele [149].…”
Section: Informing About Vaccination Strategies (Ii): B Cell Receptormentioning
confidence: 92%
“…BCR repertoire analyses revealed that potential VRC01-class precursor B cells are exceptionally rare [147][148][149]. In addition, allelic variation can result in the lack of naïve B cells derived from the key VH1-2*02 allele [149]. Nevertheless, eOD-GT8-reactive naïve B cells could be identified in a majority of HIV-1-negative donors (14/18) [147,148], providing repertoire analysis-based support for advancing the eOD-GT8 immunogen to be evaluated in a clinical setting.…”
Section: Informing About Vaccination Strategies (Ii): B Cell Receptormentioning
confidence: 99%